OFFSET
0,4
COMMENTS
The expansion of (1+kx^2)/(1-x-k^2*x^7) satisfies the recurrence a(n)=a(n-1)+k^2*a(n-7),a(0)=1,a(1)=1,a(2)=1,a(3)=k+1,a(4)=k+1, a(5)=k+1,a(6)=k+1 with a(n)=sum{k=0..floor(n/3), binomial(n-3k,floor(k/2))r^k}.
LINKS
Index entries for linear recurrences with constant coefficients, signature (1,0,0,0,0,0,1).
FORMULA
a(n)=a(n-1)+a(n-7); a(n)=sum{k=0..floor(n/3), binomial(n-3k, floor(k/2))}.
MATHEMATICA
CoefficientList[Series[(1+x^3)/(1-x-x^7), {x, 0, 60}], x] (* or *) LinearRecurrence[ {1, 0, 0, 0, 0, 0, 1}, {1, 1, 1, 2, 2, 2, 2}, 60] (* Harvey P. Dale, Oct 07 2018 *)
CROSSREFS
KEYWORD
easy,nonn
AUTHOR
Paul Barry, Sep 12 2004
STATUS
approved